THE USE OF COMBINATIONAL DIAGRAM DURING THE DETERMINING EXTREME FACTORS IN THE CONSTRUCTION OF BRIDGES - Artomov, V. Ye. (Science and Transport Progress, 2005)
The method of combinational profiles is used for refining the values of deformational and force factors in the designs of automobile bridges, intended for multi-lane road traffic.